2016
DOI: 10.1021/acs.est.6b03583
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Humic Acid and Its Interaction with Uranyl in the Presence of Hydrophobic Surface Implicated by Molecular Dynamics Simulations

Abstract: This work targeted a molecular level of understanding on the dynamics of humic acid (HA) and its interaction with uranyl in the presence of hydrophobic surface mimicked by a carbon nanotube (CNT), which also represents a potential intruder in the environment accompanying with the development of nanotechnology. In aqueous phase, uranyl and HA were observed to build close contact spontaneously, driven by electrostatic interaction, leading to a more compact conformation of HA. The presence of CNT unfolds HA via π… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 76 publications
5
32
0
Order By: Relevance
“…The all-atom model of the Leonardite HA was transferred to the CG model using the four-to-one mapping rule (Figure S1a,b), similar to the martinize.py script provided by the Martini force field . Although it is hard to expect a single type of model compound to represent the full features of HAs, the model used in our simulations has the typical features of real HAs, such as aromatic rings, hydroxy groups, and carboxyl groups that enable it to be amphiphilic with a flexible backbone. NP was constructed by arranging CG beads into a sphere of 10 nm in diameter. Types of CG beads on the NP surface were set according to the defined surface property (Figure S1c–f).…”
Section: Methodsmentioning
confidence: 99%
“…The all-atom model of the Leonardite HA was transferred to the CG model using the four-to-one mapping rule (Figure S1a,b), similar to the martinize.py script provided by the Martini force field . Although it is hard to expect a single type of model compound to represent the full features of HAs, the model used in our simulations has the typical features of real HAs, such as aromatic rings, hydroxy groups, and carboxyl groups that enable it to be amphiphilic with a flexible backbone. NP was constructed by arranging CG beads into a sphere of 10 nm in diameter. Types of CG beads on the NP surface were set according to the defined surface property (Figure S1c–f).…”
Section: Methodsmentioning
confidence: 99%
“…Several experimental and modeling studies reported the effect of humic acid (HA) and fulvic acid on U mobility through adsorption and complexation. 13,14,24,31 However, there are limited studies reporting adsorption and desorption of U onto NOM. 24,32 The adsorption of U−humic complexes onto quartz was enhanced between pH 3 and 6.…”
Section: Effect Of Nom On U Solubility Experiments At Phmentioning
confidence: 99%
“…The TNB monomeric model was used in FFMD simulation of interactions of HAs with several explosive species (e.g., trinitrotoluene) by Schutt and Shukla (2020). The older Stevenson HA model (Stevenson, 1994) was used in the FFMD simulation of HA interactions with uranyl and graphene oxide (Lan et al, 2016(Lan et al, , 2019.…”
Section: Modeling Of Som Its Interactions In Soils and Associated Cha...mentioning
confidence: 99%